THE IMPACT OF CARDIAC REHABILITATION ON FRAILTY SEVERITY. (11th November 2018) - Kehler, D; Giacomantonio, N; Firth, W; Rockwood, K; Theou, O
Abstract: We aimed to determine if cardiac rehabilitation reduces frailty levels from admission to program completion. Data from 250 patients with stable cardiovascular disease referred for rehabilitation were analyzed. Participants engaged in a 12-week group-based exercise and education program 2x/week. Frailty was measured with a 24-item frailty index. Frailty severity was assessed using clinically meaningful frailty index cut-offs (<0.20, 0.20–0.30, 0.30–0.40, and >0.40). Improvement in frailty was defined as a reduction in frailty index scores by ≥0.03 (minimal important difference). Frailty levels were calculated in 179 patients at baseline and program completion (mean age: 61.7 ± 11.0; 27.5% female); 4.5%. 26.3%, 25.7%, and 43.6% met the <0.20, 0.20–0.30, 0.30–0.40, and >0.40 frailty severity categories, respectively. Frailty scores were significantly reduced from baseline (0.38 ± 0.12) to program completion (0.31 ± 0.12; p<0.0001); 66% of participants improved their frailty scores. Compared to participants in the two lowest frailty severity groups, age and sex-adjusted linear regression models demonstrated that patients with a frailty index score of 0.30–0.4 did not have a greater relative improvement in frailty at the end of the program; whereas the highest severity group (>0.40) had a significantly greater relative change (β-coefficient: -0.07, 95% CI: -0.04 to -0.10; p<0.0001). Improvement in a minimal important frailty index score change at program completion was achieved by 25%, 53%, 70%, and 76%, across the frailty severity categories, respectively (p<0.0001). Cardiac rehabilitation can significantly reduce frailty levels in patients with cardiovascular disease (by ~1.7 fewer deficits). Patients with more severe frailty levels may derive the most benefit from cardiac rehabilitation.